Georgi Dimitrov 1882-1949. [Săst.: N. Simeonova, Z. Lapteva, E. Kabakčieva, i T. Ignatova] (Izd. na BKP, 1970)
Institut po istorija na BKP pri CK na BKP. Centralen muzej "Georgi Dimitrov". Kăšta-muzej "Georgi Dimitrov"